Think-Aloud Protocol Analysis: Revealing The Student's Problem in Reading Comprehension - Ni Wayan Krismayani; Sebastianus Menggo (Universitas Hamzanwadi, 2022)
Readers should integrate information from the text they are reading with their existing knowledge since reading is a process of building meaning and language expansion. Without improving reading abilities, it is hard to succeed in the teaching and learning process and develop a more thorough understanding, a perceptive attitude, and creative thinking to reach reading achievement. The purpose of this study is to outline the issues that cropped up while reading. In this descriptive-qualitative study, the researchers identified, analyzed, and characterized the readers' mental processes for reading comprehension. Thirty students were taken randomly from three classes enrolled in the Intermediate Reading Course of the English Language Education Study Program, Universitas Mahasaraswati Denpasar. The finding showed that the students encountered four main problems: Inability to understand word, phrase, and sentence processing (78.1%); having weak syntactic parsing (83.3%), less inference (81.7), and inadequate self-monitoring (84%). The reading lecturers are suggested to determine the student’s reading comprehension needs and employ relevant tips in the reading course, such as creating good connections, making predictions, visualizing, making inferences, self-questioning, and summarizing. The results are expected to give a useful contribution to strengthen reading theory and the lecturers in analyzing students’ reading comprehension problems.